Medium-term outcome and classification of traumatic anterior hip dislocations. Issue 6 (November 2021) - Yaari, Lee S; Kadar, Assaf; Shemesh, Shai; Haviv, Barak; Leslie, Michael P
Introduction: Traumatic anterior hip dislocations are subdivided to obturator (inferior) and pubic (superior) dislocations by Epstein's descriptive classification. This rare injury is thought to have favourable clinical outcomes. The incidence of associated femoral head and acetabular injuries has been low in past case series. We sought to revisit this injury and classification in the era of advanced imaging and contemporary surgical techniques. Materials and methods: A retrospective study of 15 patients treated for anterior hip dislocation was performed. Medical records were reviewed for demographic and surgical data. Imaging studies were revisited to determine direction of dislocation and associated fractures. Patients were assessed for pain, hip function using the modified Harris Hip Score (mHHS), hip range of motion and radiographic changes. Mean follow-up time was 3 years. Results: Anterior dislocation occurred in an obturator (inferior), pubic (superior) or central direction. 9 patients had concomitant femoral head impaction and 7 patients suffered from acetabular fractures. 8 patients with an anterior hip dislocation underwent surgical treatment. This therapy, along with early range of motion and weight bearing, produced favourable clinical outcomes with 9 patients reporting no pain and an average mHHS of 83.8. 6 patients had heterotopic ossification at latest follow-up. Conclusions: Traumatic anterior hip dislocation is commonly associated with femoral head impaction and acetabular injuries which should be addressed operatively when appropriate to produce favourable results. In this paper, we propose a revision to the commonly used descriptive classification system.